IMPLICATIONS OF FUNCTIONAL POSITIONS IN THE CAREER DEVELOPMENT OF APPARATUS IN INDONESIA - Yohanes Susanto; Bai Sangkut (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2024)
Organizational commitment to apparatus career development is an interesting issue in the current literature in Indonesia. This study investigates how government organizational commitment and apparatus career development are influenced by the implementation of functional positions, administrative positions, and staffing regulations. Furthermore, it is an effort to strengthen understanding of the pathways and conditions to fulfil apparatus career development by assessing the role of the job of moderating the improvement of apparatus competency and organizational commitment. This study encourages the use of structural equation modelling using a cross-sectional approach to evaluate hypotheses using information gathered from 350 local government employees in the Indonesian city of Lubuklinggau, South Sumatra. The results show that organizational commitment is a mediator in career growth between apparatus functional jobs and administration ones. Additionally, the relationship between personnel policies and the advancement of the apparatus is moderated by the effect of improving apparatus competence. This research contributes significantly to helping determine how the functional positions of apparatus, organizational commitment, and career development of apparatus are intertwined by highlighting the important role of implementing functional positions, with staffing regulations and supported by increased competence of apparatus